2003
DOI: 10.1136/heart.89.6.633
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive intravenous coronary angiography using electron beam tomography and multislice computed tomography

Abstract: Background: Electron beam computed tomography (EBCT) and multislice computed tomography (MSCT) are both suitable for non-invasive identification of coronary stenoses. Objective: To compare intravenous coronary EBCT angiography (EBCTA) and MSCT angiography (MSCTA) with regard to image quality and diagnostic accuracy. Methods: EBCTA was done using an Imatron C-150 XP scanner in 101 patients following a standard protocol (slice thickness 3 mm, overlap 1 mm, acquisition time 100 ms, prospective ECG trigger). For M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 17 publications
2
49
1
2
Order By: Relevance
“…Still, our results are very similar to those obtained in the few available comparisons between MSCT and MRI (13,14). Third, in the present study, 14% of coronary segments were uninterpretable, which is in line with previous studies (6,11,22). However, with the introduction of 32-and 64-slice systems, the percentage of uninterpretable segments is likely to decline further.…”
Section: Left Ventricular Functionsupporting
confidence: 81%
See 1 more Smart Citation
“…Still, our results are very similar to those obtained in the few available comparisons between MSCT and MRI (13,14). Third, in the present study, 14% of coronary segments were uninterpretable, which is in line with previous studies (6,11,22). However, with the introduction of 32-and 64-slice systems, the percentage of uninterpretable segments is likely to decline further.…”
Section: Left Ventricular Functionsupporting
confidence: 81%
“…A promising new imaging technique for the noninvasive detection of CAD is multislice computed tomography (MSCT), which allows the acquisition of high-quality images of the entire heart within a single breathhold. Several studies have demonstrated the technique to be useful in the detection of coronary artery stenoses with sensitivities and specificities ranging from 72 to 95% and 75 to 99%, respectively (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Initially, MDCT lacked the capacity to evaluate coronary artery stenosis, with diagnostic accuracies for four-slice MDCT ranging from 78% to 93% (3,4). Additionally, MDCT was unable to assess almost one-quarter of all coronary artery segments due to poor image quality.…”
Section: Assessment Of Significant Cad Using Mdctmentioning
confidence: 99%
“…Similar percentages have been reported previously. 13,19,27 In the near future, however, this limitation may be overcome by the introduction of 32-detector and 64-detector row scanners in combination with faster rotation times, which are likely to reduce the percentage of nonassessable segments. Second, an important drawback of MSCT is the radiation dose that is still considerably high: Ϸ8 mSv.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%